(untitled) (Progressive Agriculture, 2013)
This paper considers the comparative study to find out the farm-specific technical efficiency of the different categories of onion producing farms in Bangladesh. Cobb-Douglas stochastic frontier production function was used to estimate the parameters by using farm-level data. Some socio-economic factors like age, education, experience and plot size were taken into account in technical inefficiency effects model. The elasticity of output with respect to land and labour were 0.2077 and 0.0809 for small farm, 0.1076 and 0.0006 for medium farm and 0.0032 and 0.2406 for large farm respectively and with respect to seed, it was - 0.0089, 0.0015 and -0.0008 for small, medium and large farms respectively and with respect to irrigation, it was -0.0062, 0.3014 and 0.0721 for small, medium and large farms respectively and with respect to capital cost, it was 0.2089, -0.0072 and 0.1376 for small, medium and large farms respectively. The coefficients of age were found to be expected negative sign in small and medium farms and it was positive sign for large farm. The coefficients of experience were significant with negative sign in small and medium farms. The coefficients of education were negative in small and medium farms and it was positive for large farm. The coefficients of plot size were insignificant with positive sign in small farm. The coefficients of plot size were found to be significant with negative value in medium and large farms. The farm-specific technical efficiencies of onion producing small, medium and large farms varied from 55 per cent to 99 per cent, 57 per cent to 99 per cent and 56 per cent to 99 per cent with a mean technical efficiency of 77 per cent, 87 per cent and 84 per cent respectively, which meant that without incurring any additional costs there was a scope to increase output per hectare of onion by 23 per cent, 13 per cent and 16 per cent for small, medium and large farms respectively through the efficient use of existing production technology. DOI: http://dx.doi.org/10.3329/pa.v22i1-2.16482 Progress. Agric. 22(1 & 2): 213-221, 2011